DEVELOPMENT OF BUSINESS STRATEGIES USING QSPM AND SWOT ON SNAIL CHIPS - Lolyka Dewi Indrasari; Silvi Rushanti Widodo (Badan Penerbit Jurnal, Faculty of Engineering, Universitas Brawijaya, 2020)
Strategy in the snail chips business is the topic of this research. The purpose of this study is to determine the position of the company based on the SWOT results and the sequence of alternative strategies found on QSPM. The stages of this research were to make observations at PT.X to determine the strengths, weaknesses, opportunities, and threats of the snail product. The results obtained by the company lie in quadrant II with a suitable strategy to increase resistance to reduce the danger that comes, while the order of the choice of method is first to strengthen cooperation with new collectors, second to improve quality better than competitors, third to plan delivery schedules if the volume of demand increases. Suggestions that can be used by related companies are implementing alternative strategies on an ongoing basis and periodically evaluating them.